Simultaneous depletion of RB, RBL1 and RBL2 affects endoderm differentiation of human embryonic stem cells - Shota Nakanoh; Juned Kadiwala; Laetitia Pinte; Carola Maria Morell; An-Sofie Lenaerts; Ludovic Vallier (PLoS ONE, 2022)
RB is a well-known cell cycle regulator controlling the G1 checkpoint. Previous reports have suggested that it can influence cell fate decisions not only by regulating cell proliferation and survival but also by interacting with transcription factors and epigenetic modifiers. However, the functional redundancy of RB family proteins (RB, RBL1 and RBL2) renders it difficult to investigate their roles during early development, especially in human. Here, we address this problem by generating human embryonic stem cells lacking RB family proteins. To achieve this goal, we first introduced frameshift mutations in RBL1 and RBL2 genes using the CRISPR/Cas9 technology, and then integrated the shRNA-expression cassette to knockdown RB upon tetracycline treatment. The resulting RBL1/2_dKO+RB_iKD cells remain pluripotent and efficiently differentiate into the primary germ layers in vitro even in the absence of the RB family proteins. In contrast, we observed that subsequent differentiation into foregut endoderm was impaired without the expression of RB, RBL1 and RBL2. Thus, it is suggested that RB proteins are dispensable for the maintenance and acquisition of cell identities during early development, but they are essential to generate advanced derivatives after the formation of primary germ layers. These results also indicate that our RBL1/2_dKO+RB_iKD cell lines are useful to depict the detailed molecular roles of RB family proteins in the maintenance and generation of various cell types accessible from human pluripotent stem cells.